Gross motor development among 7 – 9 years old children in Sabah - Hasnol Noordin; Pathmanathan K. Suppiah; Abdul Muiz Nor Azmi; Angelica Joanne Joummy; Ching, Phylicia Phoa Siew; Noor Syaakira Isahak (IJPNPE, 2019)
The aim of the study was to examine the gross motor development of children between 7-9 years old in Sabah. A total of 240 children (134 boys, 104 girls) participated in this study from 2 different location; rural and urban area. The children’s proficiency in motor skills was assessed with the Test of Gross Motor Development-2 (TGMD-2). The children performed two trials for each gross motor skill which has been divided into two subtests, locomotor and object control. The results showed that there was no significant difference between boys and girls in locomotor skills (p>0.05) but there was a significant difference in one of the object control skills (overarm throw) between boys and girls (p<0.05). There were significant differences between rural and urban children in locomotor skills (run, gallop, and slide) and object control (catch and underarm roll) (p<0.05). The current study demonstrated that children in rural schools displayed better fundamental motor skills development compared to children in urban schools.